Anatomical correction of transposition of great arteries with persistent ductus arteriosus. One year after operation. Issue 1 (January 1980) - Harinck, E; Van Mill, G J; Ross, D; Brom, A G
Abstract : The postoperative data are described of a boy who had a 'switch' operation for transposition of the great arteries with persistent ductus arteriosus more than a year before. The child is living a normal active life. Electrocardiography, echocardiography, and angiocardiography show persistent abnormality of structure and function of the right ventricle but no evidence of reduced coronary blood flow, coarctation at the suture lines of the great arteries, or aortic regurgitation. Reference is made to an identical case operated upon 2 1/2 years ago.